Unaltered low nerve growth factor and high brain-derived neurotrophic factor levels in plasma from patients with fibromyalgia after a 15-week progressive resistance exercise - Anna Jablochkova; Emmanuel Bäckryd; Eva Kosek; Kaisa Mannerkorpi; Malin Ernberg; Björn Gerdle; Bijar Ghafouri (Medical Journals Sweden, 2019)
Background: The pathophysiology of fibromyalgia includes central and peripheral factors. Neurotrophins, such as nerve growth factor and brain-derived neurotrophic factor, are involved in peripheral and central nervous system development of pain and hyperalgesia. Few studies have examined circulating nerve growth factor and brain-derived neurotrophic factor in fibromyalgia or have investigated whether exercise interventions affect the levels of these peptides. Objectives: To compare plasma levels of nerve growth factor and brain-derived neurotrophic factor in fibromy-algia and in healthy controls, to investigate correlations between levels of nerve growth factor, brain-derived neurotrophic factor, and cytokines and clinical variables, and to investigate the effect of exercise on these levels. Subjects and methods: A total of 75 women with fibromyalgia participated in blood tests at baseline and after the 15-week intervention, and 25 healthy controls participated at baseline. Patients were randomized to a 15-week progressive resistance exercise intervention or a relaxation intervention. Results: Brain-derived neurotrophic factor level was significantly higher (p  < 0.001) and nerve growth factor level was significantly lower (p  < 0.001) in fibromyalgia than in healthy controls. Neither resistance exercise nor relaxation interventions affected the levels of brain-derived neurotrophic factor or nerve growth factor. No significant correlations were found between brain-derived neurotrophic factor or nerve growth factor plasma levels in fibromyalgia and cytokine levels or clinical variables. Conclusion: Changes in circulating nerve growth factor and brain-derived neurotrophic factor levels may affect nociception/pain in fibromyalgia. Clinical improvements were achieved following the exercise intervention, but the levels of brain-derived neurotrophic factor and nerve growth factor were not normalized.